1986
DOI: 10.1530/jrf.0.0780251
|View full text |Cite
|
Sign up to set email alerts
|

Infertility in mice infected genitally with a human strain of Chlamydia trachomatis

Abstract: Progesterone-treated C3H and TO mice were inoculated genitally with a human C. trachomatis strain, serovar E, designated N.I. 1 or with 2SP control medium. Of the C3H mice serving as controls 93% had litters by the end of a 6-month period compared to 31% of mice infected with chlamydiae. This infertility could not be explained by tubal occlusion, since the oviducts appeared normal at autopsy. Some of the mice were induced to superovulate. Eggs were never recovered from the oviducts on the inoculated sides of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 11 publications
1
58
0
Order By: Relevance
“…trachomatis has been assumed to be similar to the events seen in C. trachomatis infection of animals or tissue culture and in vivo chlamydial conjunctival infection. Tuffrey and coworkers (Tuffrey & Taylor-Robinson, 198 1 ;Tuffrey et al, 1982Tuffrey et al, , 1984Tuffrey et al, , 1985Tuffrey et al, , 1986) developed a mouse model of chlamydial genital tract infection using a variety of human isolates of C. trachomatis. They found that infection was enhanced by progesterone, which is thought to maintain epithelial cells on the uterine surface.…”
Section: Discussionmentioning
confidence: 99%
“…trachomatis has been assumed to be similar to the events seen in C. trachomatis infection of animals or tissue culture and in vivo chlamydial conjunctival infection. Tuffrey and coworkers (Tuffrey & Taylor-Robinson, 198 1 ;Tuffrey et al, 1982Tuffrey et al, , 1984Tuffrey et al, , 1985Tuffrey et al, , 1986) developed a mouse model of chlamydial genital tract infection using a variety of human isolates of C. trachomatis. They found that infection was enhanced by progesterone, which is thought to maintain epithelial cells on the uterine surface.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of the Chlamydia organisms to enter this physical barrier is influenced by the stage of the estrus cycle. Shedding of the endometrial epithelium during certain stages of this cycle can limit the ability of C. trachomatis to establish a robust infection (Tuffrey et al, 1986;Ramsey et al, 1999). Urethral samples of infected individuals also contain defensins that have been shown to inhibit C. trachomatis infection in vitro (Porter et al, 2005).…”
Section: Innate Immunity To C Trachomatismentioning
confidence: 99%
“…Sections were cut through various levels of the block and stained with haematoxylin and eosin. Inflammatory changes were graded from + to + + + as described by Tuffrey et al (1986a).…”
Section: Histopathologymentioning
confidence: 99%
“…Although a range of HLA-linked diseases has been described in man, only sexually acquired reactive arthritis, some cases of which have a chlamydial aetiology (Keat et al, 1987), has been strongly associated with the HLA haplotype, B27 (Keat, 1986). We have developed a mouse model of chlamydial salpingitis (Tuffrey et al, 1986a) and infertility (Tuffrey et ai, 1986b) that lends itself to the investigation of possible genetic factors that might influence susceptibility to genital chlamydial infections. Many mouse strains are genetically defined and in this paper we report investigations of the natural susceptibility or resistance of several strains of mice to chlamydial salpingitis and infertility, with emphasis on embryo implantation.…”
Section: Introductionmentioning
confidence: 99%